23rd solar cycle: Solar activity parameters and associated Forbush decreases. Issue 1 (1st January 2023) - Bhatt, Beena; Chandra, Harish
Abstract: We report Forbush decreases (FD) in cosmic ray intensity from January 1996 to December 2008, the whole Solar Cycle 23rd. Statistical analysis is done for only 152 events for which associated solar flare position, flare classes, and Coronal Mass Ejections (CME) speed are given. We applied FD parameters taken from the Forbush Effects and Interplanetary Disturbances databases maintained by the Pushkov Institute of Terrestrial Magnetism, Ionosphere, and Radiowave Propagation (IZMIRAN), obtained by processing the data of the worldwide neutron monitor network using the global survey method (GSM) (A. Belov et al., 2018 ). For the said number of events, we examine their effect on interplanetary space and the decrease of the galactic cosmic rays (GCR) near Earth. We found that the 11–20° latitudinal belt shows more FD- associated flare events than the other latitudinal belts, and on this belt, the Southern hemisphere is more active. The results reveal that FDs and solar flares are well correlated. Statistical analysis is carried out for the magnitude of the CR decrease with solar and geomagnetic parameters.